The sign of the cat - Jonell, Lynne (Square Fish, 2016)
Eleven-year-old Duncan McKay uses his ability to communicate with his companions Fia, a kitten, and Brig, a tiger, to aid him on a journey to claim his rightful place as heir to his island kingdom. Duncan is enlisted to serve a crew of pirates and sent to the far edges of his kingdom in the course of his adventurous quest.